3D fault-zone architecture across the brittle–plastic transition along the Median Tectonic Line, SW Japan: Fault-rock characterization. (December 2021) - Katori, Takuma; Shigematsu, Norio; Kameda, Jun; Miyakawa, Ayumu; Matsumura, Risa
Abstract: We determine the features and distribution of fault rocks along the Median Tectonic Line (MTL), SW Japan, to establish the 3D architecture of the fault zone across the brittle–plastic transition. Cataclasites exposed close to the lithological boundary fault (the MTL) can be divided into those formed by sinistral faulting at temperatures of ∼300 °C and those formed by dextral faulting at ∼250 °C. Mylonites distributed to the north of the cataclasites were formed by sinistral faulting and can be divided into lower-temperature mylonite (L-T mylonite) close to the MTL and higher-temperature mylonite (H-T mylonite) distant from the MTL, where deformation temperatures were lower and higher than 400 °C, respectively. Structures formed by sinistral faulting are oblique to those formed by dextral faulting, indicating that the former structures are older than the latter. Structures formed by sinistral faulting underwent deformation around the brittle–plastic transition. Thus, the MTL fault zone records deformation through a crustal section. Microstructural observations suggest that the differential stress just below the brittle–plastic transition (L-T mylonite) was ∼200 MPa and that this value may not change substantially in the deep crust (H-T mylonite). Highlights: Generate information for a km-scale 3D model of fault-zone architecture. Identify structures formed by deformation across the brittle-plastic transition. The studied fault zone records deformation through a crustal section. Results suggest considerable differential stress below the seismogenic zone.